22.5k views
2 votes
Write an explicit formula for the recursive formula shown below: A(n)=A(n-1)+3; A(1)=6

1 Answer

5 votes

Answer:


a_n=A(n)=3n+3.

Explanation:

You are given recursive formula
A(n)=A(n-1)+3, where
A(1)=6.

Find some terms of the sequence:


a_1=A(1)=6,\\ \\a_2=A(2)=A(1)+3=6+3=9,\\ \\a_3=A(3)=A(2)+3=9+3=12,\\ \\a_4=A(4)=A(3)+3=12+3=15,...

You van see that these terms form the arithmetic sequence with first term
a_1=6 and difference
d=3.

An explicit formula for n-th term of arithmetic sequence is


a_n=a_1+(n-1)d.

In your case,


a_n=6+(n-1)\cdot 3,\\ \\a_n=6+3n-3,\\ \\a_n=3n+3.

User Chm
by
5.9k points